2020
DOI: 10.1038/s41598-020-79292-0
|View full text |Cite
|
Sign up to set email alerts
|

Central dopamine D2 receptors regulate plasma glucose levels in mice through autonomic nerves

Abstract: Recent evidence suggests that the central nervous system (CNS) regulates plasma glucose levels, but the underlying mechanism is unclear. The present study investigated the role of dopaminergic function in the CNS in regulation of plasma glucose levels in mice. I.c.v. injection of neither the dopamine D1 receptor agonist SKF 38393 nor the antagonist SCH 23390 influenced plasma glucose levels. In contrast, i.c.v. injection of both the dopamine D2 receptor agonist quinpirole and the antagonist l-sulpiride increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“… 4 Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output. 24 , 25 In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation. 26 , 27 We performed a study on the role of TLR4 in the mechanism of PVN‐mediated sympathetic activation after MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output. 24 , 25 In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation. 26 , 27 We performed a study on the role of TLR4 in the mechanism of PVN‐mediated sympathetic activation after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that many cardiovascular diseases, such as MI, HF and hypertension, are characterized by reduced cardiac function due to peripheral inflammation associated with increased central sympathetic tone, while neuroinflammation of the PVN in turn leads to increased central sympathetic tone 4 . Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output 24,25 . In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of dopamine is produced in the gut by enteric neurons and intestinal epithelial cells, leading to increased dopamine concentration in the hepatic portal vein ( Xue et al, 2018 ). Interestingly, a study in mice showed that stimulation of central dopamine D 2 receptors increases plasma glucose levels by increasing hepatic glucose production through parasympathetic nerves ( Ikeda et al, 2020 ). The increased abundance of dopamine in liver may be another mechanism by which nitrate exposure mediates hepatic glucose output.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic DRD2 signaling plays an essential role in the regulation of food intake, body weight, and glucose metabolism (Yonemochi et al, 2019;Ikeda et al, 2020). Several studies have proved that a decline in central dopaminergic activity significantly influences metabolic parameters such as BMI, glucose, and lipid metabolism in humans (Brunerova et al, 2013).…”
Section: Insights From Clinical Studies On Endoplasmic Reticulum Stre...mentioning
confidence: 99%
“…A recent clinical study reported a reduction in hypothalamic dopamine D2/D3 receptor (DRD2/DRD3) availability (examined by 18 F-fluorodeoxyglucose and 18 F-fallypride positron emission tomography [PET] imaging) in unmedicated patients with SCZ (Mitelman et al, 2020), suggesting the involvement of hypothalamic DRD2/DRD3 signaling in SCZ. Reduced DRD2 signaling in the hypothalamus is known to increase food intake, body weight, and regulate glucose metabolism (Ikeda et al, 2020), suggesting that the reduced DRD2 signaling may also be related to SCZ-related metabolic disorders such as increased BMI and abnormalities in glucose metabolism. However, the mechanisms are currently incompletely understood.…”
Section: Introductionmentioning
confidence: 99%